Evaluating the binding selectivity of transthyretin amyloid fibril inhibitors in blood plasma - Purkey, Hans E. (The National Academy of Sciences, 2001)
Transthyretin (TTR) tetramer dissociation and misfolding facilitate assembly into amyloid fibrils that putatively cause senile systemic amyloidosis and familial amyloid polyneuropathy. We have previously discovered more than 50 small molecules that bind to and stabilize tetrameric TTR, inhibiting amyloid fibril formation in vitro. A method is presented here to evaluate the binding selectivity of these inhibitors to TTR in human plasma, a complex biological fluid composed of more than 60 proteins and numerous small molecules. Our immunoprecipitation approach isolates TTR and bound small molecules from a biological fluid such as plasma, and quantifies the amount of small molecules bound to the protein by HPLC analysis. This approach demonstrates that only a small subset of the inhibitors that saturate the TTR binding sites in vitro do so in plasma. These selective inhibitors can now be tested in animal models of TTR amyloid disease to probe the validity of the amyloid hypothesis. This method could be easily extended to evaluate small molecule binding selectivity to any protein in a given biological fluid without the necessity of determining or guessing which other protein components may be competitors. This is a central issue to understanding the distribution, metabolism, activity, and toxicity of potential drugs.